1985
DOI: 10.1351/pac198557111667
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial effects in composites

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1987) in gelatin, a relatively hard gel. It would be expected that the properties of the filler-matrix interface, and hence particle size, should be important (Manson 1985), but in both the above studies the effect of particle size was found to be small. Gels containing oil droplets, soft particles in a soft matrix, would also be expected to obey rheological or composite theories, but to date only the conditions required for satisfactory preparation of composites, mainly very small oil droplet size, have been established (Miura and Yamauchi 1984;Jost et ul.…”
mentioning
confidence: 84%
“…1987) in gelatin, a relatively hard gel. It would be expected that the properties of the filler-matrix interface, and hence particle size, should be important (Manson 1985), but in both the above studies the effect of particle size was found to be small. Gels containing oil droplets, soft particles in a soft matrix, would also be expected to obey rheological or composite theories, but to date only the conditions required for satisfactory preparation of composites, mainly very small oil droplet size, have been established (Miura and Yamauchi 1984;Jost et ul.…”
mentioning
confidence: 84%
“…In addition, when the temperature inside the epoxy increases due to the exothermic reaction generated in the curing process of the epoxy resin, the reaction rate that affects the cross-linking mechanism and internal mechanical stress is changed, which causes internal cavities and surface deformation [9]. Therefore, in order to improve the insufficient mechanical and thermal properties of epoxy resin, research on epoxy composites is being conducted to improve tensile strength, compression, coefficient of thermal expansion, glass transition temperature, etc., by polymerizing, dispersing rubber or adding inorganic micro-fillers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of applications generally the optimal design of interfacial regions involves tradeoffs between strength and toughness. For example, it is known that the untreated carbon has very poor adhesion to epoxy and good adhesion can be accomplished by treating its surface and by using proper coupling agents (e.g., variety of silanes) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In other bonded materials the interfacial regions having their own structure and thickness may develop as a result of surface preparations and coupling agents used in processing. For example, in many of the polymer matrix composites very near the interface crystallization of the polymer or copolymerization of the matrix and the coupling agent seems to produce a highly oriented region with a columnar or lamellar structure which may generally be modeled as a thin orthotropic layer (e.g.. PEEK-Carbon composites) [4]. [9].…”
Section: Introductionmentioning
confidence: 99%